Factors correlated with neuropathic pain among industrial workers in Vietnam: a multi-site cross-sectional study - Nguyen, Tham Thi; Nguyen, Huong Van; Vu, Hai Minh; Chiu, Ryan G.; Nguyen, Quang Nhat; Nguyen, Thao Thi Phuong; Nguyen, Long Hoang; Dang, Anh Kim; Do, Khanh Nam; Nguyen, Tu Huu; Nguyen, Vu; Ngo, Anh Toan; et al. (Frontiers in Public Health, 2023)
Introduction Neuropathic pain is a debilitating condition resulting from various etiologies such as diabetes, multiple sclerosis, and infection, and is associated with decreased quality of life, poor health outcomes, and increased economic burden. However, epidemiological studies on neuropathic pain have been largely limited in Vietnam. Methods A cross-sectional study was conducted on adult Vietnamese industrial workers across three manufacturing plants. Demographic, socioeconomic, occupational and health data were collected. Prevalence of neuropathic pain was assessed using the Douleur Neuropathique 4 (DN4) scale. Regression modeling was utilized to identify predictors of pain. Results Among 276 workers, 43.1 and 24.3% reported that they had suffered from spinal pain and osteoarthritis pain, respectively. In terms of work conditions, people maintaining constant posture when working from 30 to 60 min (OR = 3.15, 95% CI = 1.07; 9.29), or over 60 min (OR = 2.59; 95% CI = 1.12; 5.98) had a higher risk of suffering from spinal pain. People who worked in conditions lacking adequate lighting and with exposures to toxic chemicals were also likely to be suffering from osteoarthritis pain with OR = 4.26, 95% CI = 1.02; 17.74 and Coef. = 1.93; 95% CI = 1.49; 2.50, respectively. Regular health examinations and higher expenditure for healthcare were correlated with a lower prevalence of neuropathic pain. Discussion These results may inform the adoption of pain screening and other programs that increase health care access for this population, as well as more stringent occupational health and safety standards.